RAAS inhibitors are associated with a better chance of surviving of inpatients with Covid-19 without a diagnosis of diabetes mellitus, compared with similar patients who did not require antihypertensive therapy or were treated with other antihypertensives - Khalangot, Mykola; Sheichenko, Nadiia; Gurianov, Vitaly; Zakharchenko, Tamara; Kravchenko, Victor; Tronko, Mykola (Frontiers in Endocrinology, 2023)
Purpose The effect of renin-angiotensin-aldosterone system (RAAS) inhibitors in combination with COVID-19 and diabetes mellitus (DM) remains unknown. We assessed the risk of death in COVID-19 inpatients based on the presence or absence of DM, arterial hypertension (AH) and the use of RAAS inhibitors or other antihypertensives. Methods The results of treatment of all adult PCR-confirmed COVID-19 inpatients (n = 1097, women 63.9%) from 02/12/2020 to 07/01/2022 are presented. The presence of DM at the time of admission and the category of antihypertensive drugs during hospital stay were noted. Leaving the hospital due to recovery or death was considered as a treatment outcome. Multivariable logistic regression analysis was used to assess the risk of death. Patients with COVID-19 without AH were considered the reference group. Results DM was known in 150 of 1,097 patients with COVID-19 (13.7%). Mortality among DM inpatients was higher: 20.0% vs. 12.4% respectively (p=0.014). Male gender, age, fasting plasma glucose (FPG) and antihypertensives were independently associated with the risk of dying in patients without DM. In DM group such independent association was confirmed for FPG and treatment of AH. We found a reduction in the risk of death for COVID-19 inpatients without DM, who received RAAS inhibitors compared with the corresponding risk of normotensive inpatients, who did not receive antihypertensives: OR 0.22 (95% CI 0.07–0.72) adjusted for age, gender and FPG. Conclusion This result raises a question about the study of RAAS inhibitors effect in patients with Covid-19 without AH.